1988
DOI: 10.1136/gut.29.8.1098
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological constriction of the lower oesophageal sphincter: a simple method of arresting variceal haemorrhage.

Abstract: SUMMARY The effect of pharmacological constriction of the lower oesophageal sphincter (LOS) on oesophageal varices was investigated in an experimental study followed by a controlled clinical trial. In the experimental study intravariceal pressure was measured just above the LOS in 11 patients before and after constricting the LOS by intravenous pentagastrin. Intravariceal pressure fell from a mean of 23 (range 12-36)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In theory they could reduce the blood How through the varices. Metoclopramide reduces transmural esophageal variceal pressure but has no effect on portal haemodynamics [49], Although a small study by Hosking et al [50] suggested metoclopramide could reduce bleeding, this has not been confirmed in other studies. Feu ct al.…”
Section: Pharmacological Controlmentioning
confidence: 68%
“…In theory they could reduce the blood How through the varices. Metoclopramide reduces transmural esophageal variceal pressure but has no effect on portal haemodynamics [49], Although a small study by Hosking et al [50] suggested metoclopramide could reduce bleeding, this has not been confirmed in other studies. Feu ct al.…”
Section: Pharmacological Controlmentioning
confidence: 68%
“…This is in agreement with a preliminary report by Kleber et al [11], who found a 16% decrease in IOVP 20 min after intravenous metoclo pramide. This suggests that the recently de scribed beneficial effect of metoclopramide on bleeding from oesophageal varices [6] might be due to the reduction in IOVP in duced by metoclopramide. However, a pre liminary report by Feu et al [12] indicates that metoclopramide is not effective in the prevention of oesophageal rebleeding.…”
Section: Discussionmentioning
confidence: 93%
“…This finding has not been confirmed by other investiga tors [10], The recent improvement of the technique for the determination of IOVP by Staritz et al [8] has provided a valuable tool to better understand the haemodynamics of oesophageal varices. Recently Hosking et al [6] found a marked IOVP drop after con stricting LOS by intravenous pentagastrin. In our study, metoclopramide, which in creases LOS pressure by acting on receptors other than those for pentagastrin, was also found to significantly decrease IOVP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons can only be made with drugs has been shown to reduce transmural oesophageal variceal pressure, but has no effect on portal haemodynamics in a selected group of patients who have the same severity of bleeding, and the available trials do not address this [78]. A single small study suggested that metaclopramide could reduce bleeding at the time of endoscopy [79], but question. Furthermore, it is difficult to justify such studies today.…”
Section: Metoclopramide and Domperidonementioning
confidence: 99%